2007
DOI: 10.1128/aem.00351-06
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Microbial Contamination of Food from Prevalence and Concentration Data: Application to Listeria monocytogenes in Fresh Vegetables

Abstract: A normal distribution and a mixture model of two normal distributions in a Bayesian approach using prevalence and concentration data were used to establish the distribution of contamination of the food-borne pathogenic bacteria Listeria monocytogenes in unprocessed and minimally processed fresh vegetables. A total of 165 prevalence studies, including 15 studies with concentration data, were taken from the scientific literature and from technical reports and used for statistical analysis. The predicted mean of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…The samples analyzed in this study were not naturally contaminated with Listeria spp. when tested by both approaches, in agreement with a recent study that showed the low incidence of L. monocytogenes (À2.63 viable Log per gram) in leafy vegetable salads (Crépet, Albert, Dervin, & Carlin, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…The samples analyzed in this study were not naturally contaminated with Listeria spp. when tested by both approaches, in agreement with a recent study that showed the low incidence of L. monocytogenes (À2.63 viable Log per gram) in leafy vegetable salads (Crépet, Albert, Dervin, & Carlin, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…and observed distributions (PG, PLN, etc.). It should be noticed that in the heterogeneous Poisson framework used in this study, the zero counts or non-detections and the positive counts arise from the same trials (production batches), unlike the meta-analytical method proposed by Crepet et al (2007) whereby the prevalence (zero counts) component and the counts component originated from a number of different studies. However, with their methodology the integration of the prevalence studies in the counts model was attained at expenses of an overestimation in bacterial concentration since a positive value (i.e., a positive sample) was imputed in the prevalence data consisting only of zero counts in order to estimate the concentration from a prevalence value.…”
Section: Resultsmentioning
confidence: 91%
“…Finally, as both measures of dispersion were estimated using data pooled from different production batches, the dispersion factor (1/k) and the standard deviation values are expected to be higher than their respective measures representing only the heterogeneity within a batch. Although the assumption of data normality of bacterial counts has been applied for long time (Crepet, Albert, Dervin, & Carlin, 2007;Kilsby, Aspinall, & Baird-Parker, 1979;Kilsby & Pugh, 1981;Legan et al, 2001), and in many cases, supported by experimental evidence (Gill, McGinnis, & Badoni, 1996;Peleg & Horowitz, 2000), some concerns have been lately raised in that it does not allow complete absence of microorganisms and that the presence of zero counts in more than 15% of the samples complicates the fitting method (Corradini et al, 2002;Gill, Deslandes, Rahn, Houde, & Bryant, 1998), which is of significance when modelling microorganisms present in low concentrations such as pathogens. Ignoring non-detects, substituting them with the limit of enumeration or limit or quantification, or half of them (a rather common practice known as 'imputation'), are typical sources of bias in the analysis, and normally tend to overestimate the mean values (Hirano et al, 1994;Hornung & Reed, 1990).…”
Section: Resultsmentioning
confidence: 98%
“…The concentration variable was described by lognormal distribution (μ, σ). This probability is assumed to follow a Poisson distribution (Crépet et al 2007): P c = 1 -e (-NC) Eq. (2) The prevalence (P s ) of contaminated sample depends on numbers of both contaminated samples (s) and sample size (k).…”
Section: Discussionmentioning
confidence: 99%